2006
DOI: 10.1182/blood-2006-03-001164
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous small B-cell clones

Abstract: The detection of a monoclonal immunoglobulin in serum or urine usually raises concerns about the size of the underlying B-cell-derived clone and possible systemic effects caused by its expansion. However, a small clone can synthesize a very toxic protein, producing devastating systemic damage and protean clinical presentations. The resulting "monoclonal componentrelated diseases," although difficult to diagnose, may be progressive and even fatal. The monoclonal protein can aggregate and deposit systemically as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
280
1
16

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 394 publications
(305 citation statements)
references
References 109 publications
5
280
1
16
Order By: Relevance
“…1 The natural history of this disease is primarily determined by the severity of cardiac dysfunction. 2 Patients who present with advanced heart involvement, defined by very high levels of the cardiac biomarker N-terminal pro-natriuretic peptide type-B (NT-proBNP), survive only a few months and represent the most difficult challenge for treating physicians.…”
Section: Introductionmentioning
confidence: 99%
“…1 The natural history of this disease is primarily determined by the severity of cardiac dysfunction. 2 Patients who present with advanced heart involvement, defined by very high levels of the cardiac biomarker N-terminal pro-natriuretic peptide type-B (NT-proBNP), survive only a few months and represent the most difficult challenge for treating physicians.…”
Section: Introductionmentioning
confidence: 99%
“…In primary (AL) amyloidosis, not only is survival dependent on the presence of cardiac involvement but heart dysfunction also limits the feasibility of intensive and effective therapy [1]. The advent of dexamethasone-based regimens, particularly the combinations with melphalan (M-Dex) [2,3] and with cyclophosphamide and thalidomide (CTD) [4], offered patients with advanced disease effective and less toxic alternatives to autologous stem cell transplantation (ASCT).…”
Section: Introductionmentioning
confidence: 99%
“…However, the notion that a malignancy, such as MM or lymphoma, is necessary for the development of kidney disease is no longer valid. Many kidney lesions are, in fact, associated with low-grade plasma cell dyscrasia or lymphoproliferative disorders rather than their malignant counterpart (2). In a large study of patients with Ig light-chain (AL) amyloidosis, 40% were found to have .10% plasma cells in the marrow, but only 8% had evidence of MM (3).…”
Section: The Role Of Monoclonal Proteins In Kidney Diseasesmentioning
confidence: 99%